Dealing with Colonial Past - Antonina Łuszczykiewicz (Politeja, 2019)
This paper is dedicated to reconstructing the image of the British colonial rule in India in modern Hindi cinema. The main stress in the analysis is laid upon the depiction of the political and cultural impact of the British rule on common Indian people, as well as the colonizers’ attitude towards the independence movement. Consequently, the author intends to enquire, how movies made after 2000 – among which Lagaan: Once Upon a Time in India (2001), Mangal Pandey: The Rising (2005), Water (2005) and Rang De Basanti (2006) are given special attention – deal with the difficult colonial past from an over 50-year-long perspective. Moreover, the author explains, how modern Hindi cinema shapes Indian viewers’ opinions on the British rule, intending to strengthen their patriotic feelings and national pride.